Clypeodytes geiseri sp. n., an enigmatic Bidessini from Laos (Coleoptera: Dytiscidae, Bidessini). Issue 4 (2nd October 2018) - Hendrich, Lars; Brancucci, Michel; Balke, Michael
ABSTRACT: Here, we describe Clypeodytes geiseri sp. n. from Champasak Province in southwestern Laos. This very distinct species belongs to the subgenus Hypoclypeus Guignot, 1950 and can be distinguished from all other Clypeodytes species by its larger size and almost completely blackish or dark ferrugineous dorsal surface, except for some weak testaceous markings on the elytra. The habitus and the median lobe of the new species are illustrated, and a map is provided. Altogether, six species of subgenus Hypoclypeus are now known from Asia. urn:lsid:zoobank.org:pub:FC01425F-9D3A-482E-8FE4-D2BF3D4943DF